2011
DOI: 10.1128/jb.05339-11
|View full text |Cite
|
Sign up to set email alerts
|

Active Role of the Interdomain Linker of AraC

Abstract: The classical genetic studies of Englesberg and collaborators (5,6,32) showed that the product of the Escherichia coli araC gene positively and negatively regulates expression of the araBAD genes in response to the presence of arabinose. Subsequent biochemical and biophysical studies have provided in vitro assays for the protein's activities and have provided much information about the structure, properties, and function of the protein (reviewed in references 28 and 29). Each monomer of the dimeric AraC protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…The results are striking in that nearly any substitution lacking proline behaves as wild type, and nearly any substitution in the linker containing proline is impaired in its repression abilities. Because of this and an earlier finding that introduction of a proline residue into the linker region resulted in impaired repression, we also explicitly generated proline substitutions in each of the linker residues 168–172, Table . Repression in each of these was also impaired.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results are striking in that nearly any substitution lacking proline behaves as wild type, and nearly any substitution in the linker containing proline is impaired in its repression abilities. Because of this and an earlier finding that introduction of a proline residue into the linker region resulted in impaired repression, we also explicitly generated proline substitutions in each of the linker residues 168–172, Table . Repression in each of these was also impaired.…”
Section: Resultsmentioning
confidence: 99%
“…In light of the failures to detect an arm‐DBD interaction we have extended consideration to the possibility that the binding of arabinose, either directly via the N‐terminal arms or indirectly, affects the inter‐domain linker, residues 168–174, that connects each dimerization domain and a DNA binding domain. Although initial genetics experiments suggested that the repressing and inducing activities of AraC are not sensitive to sequence alterations in the linker, more recent and more precisely targeted mutational and biophysical studies have indicated that some mutations in the linker can reduce the protein's ability to repress p BAD . This article describes an expanded genetic analysis of linker mutations and fluorescence anisotropy measurements that show that binding of arabinose to the dimerization domain alters the motion of a conjugated fluorophore.…”
Section: Introductionmentioning
confidence: 99%
“…Protein members of the AraC family have two structural domains: the C-terminal DNA binding domain and the N-terminal signaling domain, connected by a relatively unstructured linker (Mahon et al, 2010;Seedorff and Schleif, 2011). The DNA binding domain comprises a ca.…”
Section: Introductionmentioning
confidence: 99%
“…AraC is composed of an N-terminal arabinose-binding and dimerization domain and a C-terminal DNA-binding domain. The expression of the araBAD operon and the AraC-encoding gene (araC), which are divergently transcribed, is repressed by binding of AraC to the promoter region forming a DNA loop in the absence of L-arabinose (13)(14)(15). In the presence of L-arabinose, three promoters, ParaBAD, ParaE, and ParaFGH, are activated, and ParaC is derepressed (16).…”
mentioning
confidence: 99%